"PENUGASAN BADAN USAHA MILIK NEGARA DALAM PENGUSAHAAN JALAN TOL" (Studi: Penugasan PT Hutama Karya (Persero) Dalam Pengusahaan Jalan Tol Di Sumatera) - Agus Riyanto, (2021)
Abstract This study aims to examine the implementation of Government programs in the context of accelerating the development of Regions in Sumatra. The main problem is that the Government has assigned PT. Hutama Karya (Persero) to operate toll roads on 24 Toll Roads in Sumatra that are economically feasible but overall are not financially viable. In this study raises the question whether the assignment can be given to PT. Hutama Karya (Persero) as a State-Owned Enterprise (BUMN) in the form of a Persero for the operation of 24 Toll Roads in Sumatra? This research was conducted using the juridical normative method with reference to the general principles of good governance (AUPB) theory. The solution of this research is how the Government should be able to appoint PT. Hutama Karya (Persero) by taking into account AUPB and not in conflict with regulations in the toll road infrastructure sector.